IT Capability’s Impact Towards Competitive Advantage Through Business Process Agility on Indonesia’s Accounting Firms during Pandemic - Setiawan, Aulastine; Yuliana, Oviliani Yenty; Devie, Devie (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2022)
The existence of work from home policy due to the Covid-19 pandemic had caused several service industry sectors, such as accounting firms, to be hardly affected. However, to survive in the business competition, these accounting firms have to adapt by increasing their IT capability and business process agility to create a competitive advantage over their competitors. This research aims to observe the IT capability and the agility of Indonesia’s accounting firms and examine the mediation effect of business process agility. The samples are public accounting firms registered in Indonesia’s Audit Board and a service accounting firm with more than one licensed accountant. The analysis technique used in this research is Structural Equation Modelling with three variables: IT Capability, Business Process Agility, and Competitive Advantage. The results show that IT Capability directly impacts the Competitive Advantage of the firms, and the mediation of Business Process Agility increases the total effect of IT Capability towards competitive advantage. Therefore, this study could acknowledge Indonesia’s accounting firms about how to survive in this pandemic by creating a Competitive Advantage by increasing their IT Capabilities and Business Process Agility. Adanya kebijakan work form home akibat pandemi Covid-19 telah memberikan dampak yang berat pada sektor industri jasa, salah satunya adalah kantor akuntan publik. Agar tetap dapat bersaing, kantor akuntan harus mampu beradaptasi dengan meningkatkan kapabilitas IT (IT Capability) dan kelincahan bisnis proses (Business Process Agility) untuk menciptakan keunggulan kompetitif (Competitive Advantage) atas pesaingnya. Penelitian ini bertujuan untuk menguji IT Capability dan Business Process Agility kantor akuntan di Indonesia serta menguji pengaruh mediasi dari Business Process Agility. Sampel penelitian adalah kantor akuntan publik yang terdaftar di IAI dan kantor akuntan jasa yang memiliki lebih dari satu akuntan yang berpraktik. Teknik analisis data yang digunakan dalam penelitian ini adalah Sturctural Equation Modelling dengan tiga variabel: IT Capability, Business Process Agility, dan Competitive Advantage. Hasil penelitian menunjukkan bahwa IT Capbility berdampak secara langsung terhadap Competitive Advantage perusahaan dan mediasi Business Process Agility memperkuat pengaruh IT Capability terhadap Competitive Advantage. Untuk itu, penelitian ini memberikan wawasan kepada kantor akuntan di Indonesia tentang bagaimana cara bertahan di masa pandemi Covid-19 dengan menciptakan Competitive Advantage melalui IT Capabilities dan Business Process Agility.